Menstrual cycle characteristics, perceived impact on performance, and barriers to communication: Perspectives of high-performance adolescent athletes in Singapore - Taim, B. C.; Lye, J. Suppiah, H. T.; Chan T. W.; Chia, M. Clarke, A. (Scandinavian Journal of Medicine & Science in Sports, 2024)
The purpose of this study was to examine the menstrual cycle (MC) characteristics, explore the impact on performance, and identify barriers to and facilitators of MC-related communication among high-performance female adolescent athletes in Singapore. Ninety athletes (15.4 ± 1.8 years) from multiple sports completed an online questionnaire. Eighty-four athletes were postmenarcheal (menarcheal age 11.9 ± 1.3 years), including two who were using an oral contraceptive pill (OCP). Secondary amenorrhea, current or history of, was self-reported in 16% of athletes. Sixty-two percent and 67% of non-OCP athletes perceived that the MC affected their ability to train and compete, respectively. Athletes preferred speaking to a parent (85%) and a female figure (67%) about MC-related concerns. Through thematic analysis, three barriers to communication were constructed: (1) pervasive menstrual stigma, (2) constraints of the training environment, and (3) the low value placed on MC-related conversations. Two facilitators of communication were constructed: (1) respect athletes' individual experiences as menstruating girls and (2) foster a safe space for MC-related conversations. Findings demonstrated that menstrual irregularities are common in adolescent athletes and screening for MC disorders, particularly primary amenorrhea should be undertaken in this population, with clear support pathways for management including symptom mitigation. To support athletes in raising MC-related concerns when needed, structured communication pathways that consider individual preferences and involve a (female) point of contact should be established within the training environment. Improving menstrual health literacy among adolescent athletes before any misinformation or negative perceptions are firmly established may contribute to longevity in their athletic careers.